Influência das interações entre leveduras e bactérias contaminantes no rendimento da fermentação etanólica - Papin, Larissa Ferreira (Universidade Federal de São Carlos, 2024)
Brazil is recognized worldwide for its pioneering role in integrating ethanol into its energy matrix, produced via fermentation using yeast strains, particularly Saccharomyces cerevisiae, and sugarcane juice or molasses. The industrial production of ethanol in Brazil is characterized by a non-aseptic process, where the must (a mixture of juice, molasses, and water) doesn´t pass through any type of treatment that aimed to eliminate microbial contamination. Due to these characteristics of the fermentation process in Brazil, one of the factors that can influence fermentation yield is bacterial contamination, which tends to have detrimental effects on the process due to competition for nutrients. However, the interaction between yeasts and contaminating bacteria found in the process is not fully elucidated and may not be entirely harmful, with a complex and dynamic synergy related to the metabolites formed. In this context, the present study proposes to evaluate the impact of interactions between yeasts and bacteria on fermentation yield, cell growth, ethanol production, and by-products. For this purpose, mixed fermentations were conducted in semi-synthetic medium between the yeast Saccharomyces cerevisiae and four different contaminants commonly found in the sugarcane industry. Limosilactobacillus fermentum, Lactobacillus helveticus, Lactiplantibacillus plantarum, and Lactobacillus amylovorus were studied at four cell concentrations (105, 106, 107, and 108 cells per mL) in consortium with the yeast. Ethanol, sugars, acetic acid, lactic acid, and glycerol were quantified, in addition to the biomass formed. The research showed that Limosilactobacillus fermentum negatively affected yeast cell growth and fermentation efficiency, while Lactobacillus helveticus, even though not remaining until the end of fermentation, caused a reduction in efficiency, with high levels of lactic acid, exceeding those in the L. fermentum trials. L. plantarum did not demonstrate the positive synergies reported in the literature, while Lactobacillus amylovorus contributed to increased fermentation efficiency and cell growth. The results emphasize the importance of understanding microbial interactions to optimize ethanol production and demonstrate that there are different forms of synergy among microorganisms, influenced by the medium and cell concentration.
INFLUENCE OF INTERACTIONS BETWEEN YEASTS AND CONTAMINATING BACTERIA ON ETHANOL FERMENTATION YIELD
Keywords: Fermentação; Contaminação bacteriana; Levedura; Rendimento; Fermentation; Yeast; Contamination; Yield; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::MICROBIOLOGIA DE ALIMENTOS; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::ENGENHARIA DE ALIMENTOS; CIENCIAS BIOLOGICAS::MICROBIOLOGIA